Capital markets development, financial structure and economic development in Africa - Mahonye, Nyasha (My University, 2014)
This dissertation examines the evolution of Africa’s capital markets, and the determinants of their stock markets and banking sectors development. It also ascertains the linkages between financial structure and economic development of selected 15 African countries. These largely adaptive and innovative empirical analyses record some interesting results. We find a trend towards market-based financial systems in most African economies (Chapter 3). Though both equity markets and banks have been deepening in the last decade, the trend is stronger for markets than for banks. There is still however large domination of traditional banking finance, because the recorded trending towards markets is mainly driven by a rise in equity market size (capitalization) and less so by trading activities in these markets. There is a wide cross-country variation in financial system depth and, in banking sector and stock market development in Africa, with South Africa and North African countries in our sample featuring relatively large markets. Additional findings suggest that banking sector development, GDP per capita, private capital flows; domestic investment, trade openness, FDI, interest rate and inflation are important determinants of stock market development (Chapter 4). Specifically, institutional quality has a positive effect on stock market development, especially regulatory quality. Corruption and government effectiveness have negative effects on stock market development, with the latter finding being theoretically counter-intuitive. For banking sector development, GDP per capita, remittances, domestic investment, exchange rate and FDI are important determinants. We also confirm that the relationship between stock market development and the banking sector development for a sample of African countries is positive, indicating that financial intermediaries and stock markets are complements, not substitutes. In agreement with extant empirical evidence, we find that financial structure does not matter in determining economic development; instead, it is level of financial services that positively and significantly determine economic development in selected African countries (Chapter 5). The policy implication that emerges here is that relevant authorities should invest in accumulating both quantity and quality financial services in order to impact economic development in Africa without necessarily a concern for the forms of the financial services.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law & Management, School of Economic and Business Sciences, 2014.